HoSPITAL ACQuIReD PneuMonIA onSeT DAN BAKTEREMIA - Bellya Affan Roes; Dewi Kartika; Basti Andriyoko (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Hospital acquired pneumonia (HAP) is significantly impact the patient morbidity and mortality that cause etiologic identification becomes a microbiological emergency in HAP. The etiologic identification based on the onset of pneumonia is important to determine the specific pathogens, that impact patient prognosis and prevent bacteremia. The aim of the study is to know the bacterial profile and antibiotic susceptibility pattern of early onset HAP by determination, late onset HAP and HAP with bacteriaemia in the intensive care setting. The design of this study was retrospective descriptive. The data was collected from the Clinical Microbiology Laboratory, Department of Clinical Pathology and the medical record from Dr. Hasan Sadikin hospital Bandung, from April 2013–March 2013. From the 61 episodes of HAP, 18 were early onset HAP and 43 were late onset HAP, including five (5) related to (8.2%) HAP with bacteriaemia. Klebsiella pneumoniae is the most common etiology of the early onset HAP (22.2%), with the highest susceptibility (75%) to amikacin, meropenem, and tigecyclin. Acinetobacter baumannii is the most common etiology of the late onset HAP (27.9%), with the highest susceptibility (75%) to amikacin and cotrymoxazole. The most common etiology of HAP with bacteriaemia is Klebsiella pneumoniae confirmed ESBL (40%) with the highest susceptibility to amikacin and meropenem (100%). Based on this study, it can be concluded that the most common bacterial profile of the early onset HAP is K. pneumoniae, while for the late onset HAP is A. baumannii, and HAP with bacteriaemia is K. pneumoniae confirmed ESBL. All of them have the highest susceptibility to amikacin.